Development of a novel triple-layer polycrystalline diamond compact - Mashhadikarimi, Meysam (2021)
The objective of this research was to obtain a triple layer Polycrystalline Diamond Compact (PDC) via the High-pressure High-temperature (HPHT) sintering method. A thin layer of WC with 20 wt.% Nb/Ni was used as an interface between the top layer of Polycrystalline Diamond (PCD) with pure Nb binder and WC 10 wt.% Co substrate. Sintering was performed at 1750 °C under 7.7 GPa of pressure. Microhardness variation was measured and microstructural/structural studies were done via SEM/EDS and XRD. The overall results showed that this new kind of PDC can be produced successfully using pure niobium as a binder for the PDC layer and no sign of graphitization was detected. It was also found that using an interface having the resemblance to both substrate and sintered diamond body caused good adhesion between layers that can potentially enhance performance and durability of PDC